Debt and Economic Growth: The Case of Indonesia - Sari, Vita Kartika (Universitas Airlangga, 2022)
Debt is an intriguing state financing to be studied and analyzed because debt can have positive or negative impacts. Sources of debt can be from the issuance of domestically-sold bonds or foreign investment. Indonesia uses debt instruments to address the fiscal gap and increase capital for economic development. This study aims to analyze the impact of debt on Indonesia's economic growth and investment during the 1970-2018 period, using the Autoregressive Distributed Lag (ARDL) method. The study found that debt had a negative effect on GDP in the short and long run. Meanwhile, it did not affect investment in the short run but had a negative effect in the long run. The study model also had good stability as a result of Cusum and Cusum of Squares testing. Thus, appropriate debt management policies are needed to support economic growth.